2013
DOI: 10.1007/s10895-013-1161-6
|View full text |Cite
|
Sign up to set email alerts
|

Long Wavelength Fluorescence Ratiometric Zinc Biosensor

Abstract: A protein-based emission ratiometric fluorescence biosensor is described that exhibits sensitivity to free zinc ion solutions down to picomolar concentrations. Ratiometric measurements are widely used to assure accurate quantitation, and emission ratios are preferred for laser scanning microscopes such as confocal fluorescence microscopes. The relatively long emission wavelengths used are well suited to studies in tissues and other matrices which exhibit significant fluorescence background, and the apo-carboni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Again these numbers are 3 orders of magnitude higher than were determined by the Palmer group using the FRET sensors ZapCY1 and a semisynthetic carbonic anhydrase-based sensor from the Thompson group, both of which have reported values of 0.2 pM. 31,35 However, a substantially higher concentration of 72 pM was recently determined using a small molecule ratiometric fluorescent probe targeted to the mitochondria of NIH 3T3 cells. 36,37 In order to simultaneously monitor Zn 2+ in different cellular compartments in the same cell or study the relation between Zn 2+ concentration and intracellular signal transduction, sensor variants are required that can be used together with CFP-YFP based sensors.…”
Section: Calwy Sensorsmentioning
confidence: 83%
“…Again these numbers are 3 orders of magnitude higher than were determined by the Palmer group using the FRET sensors ZapCY1 and a semisynthetic carbonic anhydrase-based sensor from the Thompson group, both of which have reported values of 0.2 pM. 31,35 However, a substantially higher concentration of 72 pM was recently determined using a small molecule ratiometric fluorescent probe targeted to the mitochondria of NIH 3T3 cells. 36,37 In order to simultaneously monitor Zn 2+ in different cellular compartments in the same cell or study the relation between Zn 2+ concentration and intracellular signal transduction, sensor variants are required that can be used together with CFP-YFP based sensors.…”
Section: Calwy Sensorsmentioning
confidence: 83%
“…Recently, Zeng et al reported a long wavelength, emission ratiometric modification of the carbonic anhydrase Zn 2+ sensor that could be amenable to imaging in tissues. 160 This new system uses Alexa Fluor 594 as a FRET donor and Chesapeake Blue sulfonamide as the acceptor fluorophore. One limitation of these versions of the sensor is the requirement for microinjection or the attachment of cell-penetrating peptides to introduce it into cells, because covalent attachment of the fluorophore prevented the probe from being genetically encodable.…”
Section: Probes For Zincmentioning
confidence: 99%
“…When Zn 2+ binds carbonic anhydrase, a second cofactor (the fluorophore dapoxyl sulfonamide) binds to an open site on the Zn 2+ ion, allowing energy transfer from the dapoxyl moiety to the fluorophore on the enzyme. Recently, Zeng et al reported a long wavelength, emission ratiometric modification of the carbonic anhydrase Zn 2+ sensor that could be amenable to imaging in tissues . This new system uses Alexa Fluor 594 as a FRET donor and Chesapeake Blue sulfonamide as the acceptor fluorophore.…”
Section: Probes For Zincmentioning
confidence: 99%
“…Similarly, the decades-long clinical employment of aryl sulfonamide CA inhibitors suggests that their pharmacology is well understood and can be optimized for a given application [ 57 ]; we note that because there is no background emission from the unbound fluorescent sulfonamide, it can in principle be given systemically. We also note that we have demonstrated fluorescent sulfonamide inhibitors with emission in the infrared [ 58 , 59 ]; we view the flexibility of using different fluorescent sulfonamides as an advantage of this approach. Experiments are underway to test the sensor in a suitable animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc was removed from the protein by treatment with 2,6-dipicolinic acid at pH 7.0 in Tris buffer, essentially as previously described [ 62 ]. The Lissamine Rhodamine sulfonamide and fluorescein sulfonamide were synthesized by reaction of 4-(2-aminoethyl) benzenesulfonamide (Aldrich) with Lissamine Rhodamine sulfonyl chloride or fluorescein isothiocyanate, respectively (both Life Technologies) in pH 8.0 buffer essentially as previously described [ 58 ] and purified by silica gel column chromatography.…”
Section: Methodsmentioning
confidence: 99%